How entrepreneurs are driving sustainable development - Gimenez-Jimenez, Daniela (Emerald points., 2024)
Sustainable development aspires to reduce current societal challenges by creating wealth for everyone within the limit of the planet productive capacity, in this way, ensuring that future generations can meet their own needs. This is largely because sustainable development refers to the "development that meets the needs of the present without compromising the ability of future generations to meet their own needs". Activists, corporations, non-governmental organizations, entrepreneurs and politicians must all be involved in achieving sustainable development. Academics and policymakers have also recognized the potential of entrepreneurs for tackling current societal challenges with their businesses because entrepreneurs are able to fill the voids left by the other individuals and organizations. However, who are these entrepreneurs? How can they provide solutions and tackle current societal challenges with their business? Exploring the transformative powers of sustainable entrepreneurs, How Entrepreneurs are Driving Sustainable Development also demonstrates how family, women and immigrant entrepreneurs can tackle current societal challenges, break inequalities and bring about change.